If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12c + 3 + -9(11 + -1c) = 0 -12c + 3 + (11 * -9 + -1c * -9) = 0 -12c + 3 + (-99 + 9c) = 0 Reorder the terms: 3 + -99 + -12c + 9c = 0 Combine like terms: 3 + -99 = -96 -96 + -12c + 9c = 0 Combine like terms: -12c + 9c = -3c -96 + -3c = 0 Solving -96 + -3c = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '96' to each side of the equation. -96 + 96 + -3c = 0 + 96 Combine like terms: -96 + 96 = 0 0 + -3c = 0 + 96 -3c = 0 + 96 Combine like terms: 0 + 96 = 96 -3c = 96 Divide each side by '-3'. c = -32 Simplifying c = -32
| 3(8v+6)=210 | | 12d-9=15+9 | | 6+10d-19=2(3d+4)-1 | | 9x-(6x-4)=13 | | (3*5)t+(21-12)=15t+9 | | n^3-2n^2-15=0 | | v^2-8v+39=0 | | r^2+3r-112=0 | | 5(5x+1)= | | 5x+6y=-76 | | 7-2b-3b=2 | | 6r+4=-r-24 | | 7-2b-3b=3 | | 6-3g+2g=15 | | x^2+59x=0 | | 7x^2+11x-6=0 | | x^3-5x^2+5x-25=0 | | -2(8n-5)=106 | | 0.5(x+2)-0.8(x+2)=0.3x-0.6 | | 4x-x=0 | | 2c+3=3c-5 | | 2(3x-5)+6(x-3)=-3(4-5x)+5x-6 | | 0=16r^2+3r-9 | | y^3-512=0 | | -4+46=7(3t+6) | | -3(7n-8)=-144 | | x^2+y^2+30x+18y+297=0 | | -8*-18= | | 2x+5x=36 | | (5x-6)-(6x-4)=-1(-4+x)-4x+6 | | 4Y^2=18Y-2 | | 5x+2=90 |